PENGARUH GAYA HIDUP DAN HARGA PRODUK TERHADAP MINAT PENGGUNAAN APLIKASI SHOPEE PADA MAHASISWA MANAJEMEN KEUANGAN SYARIAH DI UIN STS JAMBI - Vivi Asnidar; Lidya Anggraeni (ICONS: Islamic Economics Journal, 2025)
This study aims to examine the influence of lifestyle and product price on the interest in using the Shopee application among students of the Sharia Financial Management Study Program at UIN Sultan Thaha Saifuddin Jambi. Using a quantitative approach with questionnaires distributed to 62 respondents, the data were analyzed through validity and reliability tests, multiple linear regression, t-test, and F-test using SPSS. The results indicate that both lifestyle and product price have a significant partial and simultaneous effect on students’ interest in using Shopee. These findings show that although students understand Islamic consumption principles, practical aspects and pricing remain key considerations in using e-commerce platforms. This study is expected to serve as a reference for students to shop more wisely and for developers to design marketing strategies that align with Muslim consumer behavior.